Explosive evolution of galaxies at high redshifts due to minor mergers - Kats, A.V.; Kontorovich, V.M. (Advances in Astronomy and Space Physics, 2013)
In the case of minor mergers analytical solutions of kinetic Smoluchowski equation with a source that corresponds to separation of galaxies from the general expansion of the universe have been found. The solutions describe the explosive evolution of galaxy mass function in the presence of the dark matter. The evolution of power-law asymptote at large redshifts is discussed.